Changes in cigarette consumption and drinking outcomes: Findings from Project MATCH - Friend, Karen B. (2005)
Individuals undergoing treatment for alcohol use disorders smoke at rates that exceed those reported in the general population, and most patients will continue to smoke after treatment completion. A growing body of research indicates that quitting smoking is associated with better alcoholism treatment outcomes. Studies that dichotomize participants into smokers and nonsmokers, however, may be overlooking the possibility that even decreases in cigarette consumption over time among continuing smokers may also be related to improved alcohol use outcomes. The purpose of this article was to examine the relationship between cigarette consumption and alcohol use outcomes using data from Project MATCH. Smokers were divided into three groups according to whether their cigarette consumption decreased, increased, or remained constant from baseline to the 15-month follow-up. Results showed that smokers whose cigarette consumption decreased were significantly less likely to relapse to alcohol use than those whose consumption increased or remained unchanged. These findings suggest that even reductions in tobacco use may be associated with better drinking outcomes in alcoholism treatment.